The risks of polypharmacy following spinal cord injury. (4th March 2017) - Kitzman, Patrick; Cecil, Darrin; Kolpek, Jimmi Hatton
Abstract : Objective : The purpose of this study was to examine the overall prevalence of polypharmacy within the spinal cord injury (SCI) population, the level of polypharmacy with respect to seven classes of high-risk drugs commonly used to treat secondary conditions in the SCI population, and the overall risks for drug-related problems (DRP) related to polypharmacy. Design : A retrospective case–control design. Setting : A commercially available claims dataset that included patient cases from 4800 hospitals in the USA between 2007 and 2009. Participants : Individuals with tetraplegia, paraplegia, and those with SCI but not specified as either tetraplegia or paraplegia as well as a control population of randomly selected, age- and sex-matched individuals without a diagnosis of SCI. Outcome measures : The overall prevalence of polypharmacy, the prevalence of commonly prescribed high-risk medications, and the prevalence of reported DRPs. Results : Overall, the patients in the SCI population were prescribed significantly more medications than their control counterparts. There was a higher rate of individuals being prescribed medications from multiple high-risk classes (e.g. analgesic-narcotics, anticonvulsant, antidepressant, and skeletal muscle relaxer), as well as multiple medications within each class (e.g. multiple analgesic-narcotics). The SCI group had a higher incidence of DRPs. Conclusion : Our results are some of the first to demonstrate the extent of polypharmacy in individuals with SCI, including commonly prescribed high-risk medications, leading to a higher rate of DPRs. The higher rate of polypharmacy and DRPs can impact rehabilitation goals and community integration following neurologic injury.